COVID-19 and gender differences in the labor market: evidence from the peruvian economy - Vaccaro, Giannina; Paredes, Tania (Pontificia Universidad Católica del Perú. Departamento de Economía, 2022)
The COVID-19 and its confinement measures have generated a severe economic contraction around the world. However, there is still no consensus on the magnitude of its immediate effects, particularly in developing countries. Analysts have emphasized not only human capital losses but also an economic recession and increase in economic and social inequalities, including gender differences. Despite the Latin America (LA) countries are most affected in terms of deaths, most studies focus on the impact of COVID-19 on developed countries. Using data from the National House- hold Surveys (ENAHO) from 2019-2021, we studied the impact of the COVID-19’S confinement measures on gender differences in the labor market in Peru, country with one of the biggest death rates. We found that the COVID-19 pandemic and its lockdown measures accentuated gender inequality in labor market. Women have largely decreased the total hours worked than men, particularly due to the reduction of formal employment. More vulnerable women are low-skilled and those who have not worked remotely.
Keywords: COVID-19 (Enfermedad); Employment; Gender differences; Impact analysis; Peru; https://purl.org/pe-repo/ocde/ford#5.02.01